EFFECT OF CINNAMOMUM BURMANNII (NEES & T. NEES) BLUME BARK ON BLOOD LIPID IN MALE WISTAR RAT - Dewanti Nugroho, Astrid
Cardiovascular disease ranks among the leading global causes of mortality, with hyperlipidemia identified as a significant contributing factor. Elevated blood lipid levels can be prevented or reduced through the use of plant-derived anti-hyperlipidemic agents. This study investigates the potential effects of cinnamon (Cinnamomum burmannii), a spice rich in cinnamic compounds believed to lower blood lipid levels. The impact of cinnamon bark powder on blood lipids was assessed in male Wistar rats through preventive and lipid-lowering tests, inducing hyperlipidemia via a high cholesterol diet. Three doses of cinnamon powder were administered: 90 (DR), 180 (DS), and 360 (DT) mg/kg body weight. Results indicate that all three doses effectively prevented the increase in blood lipids in the preventive test, with only the DS dose significantly inhibiting lipid elevation in the diseased group (Total cholesterol = 104,26 : 116,63 mg/dL; Trigliserida = 132,09 : 154,93 mg/dL; Low density lipoprotein = 51,97 : 64,09 mg/dL) after 4 weeks of administration. However, in the lipid-lowering test, none of the doses significantly reduced blood lipid levels after 2 weeks of administration. Based on this study, moderate dose cinnamon bark (180 mg/kg bw) significantly preventing blood lipid elevation. However, longer administration of the cinnamon bark powder is necessary for lowering blood lipid levels.